2021
DOI: 10.1021/acs.jpcb.1c03747
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Partially Aromatized Intramolecular Charge Transfer

Abstract: Diverse models of intramolecular charge transfer (ICT) have been proposed for interpreting the origin of the charge-transfer (CT) state in donor–acceptor (D–A) dyes. However, a large variety of fused-heterocyclic dyes containing a pseudo-aromatic ring in the rigid structure have shown to be incompatible with them. To approximate a solution within the ICT concept, we reported a novel ICT model called partially aromatized intramolecular charge transfer (PAICT). PAICT involves the generation of a CT state from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In this case, the protonation of the basic moiety may disrupt the ICT from (D) to (A), leading to a selective quenching response dependent on the protonation level (Scheme 2A). As a fundamental platform, we employed three fluorescent dyes of N 46 Previously, we demonstrated that the balance between the CT and LE states can be modulated by solvent changes, finding a dominant and intense CT state in hydrogen-donor media, such as water, methanol, and ethanol, whereas the nonhydrogen donor or low polar media favored the occurrence of the LE state (Figure 1A−C). 46 The fluorescence profiles of the dyes 3k and 3j were almost totally determined by the CT state at 476 nm and that of excited state showed to be highly stable with a prevalence inclusive in nonpolar media, such as hydrocarbons (n-hexane and n-heptane).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, the protonation of the basic moiety may disrupt the ICT from (D) to (A), leading to a selective quenching response dependent on the protonation level (Scheme 2A). As a fundamental platform, we employed three fluorescent dyes of N 46 Previously, we demonstrated that the balance between the CT and LE states can be modulated by solvent changes, finding a dominant and intense CT state in hydrogen-donor media, such as water, methanol, and ethanol, whereas the nonhydrogen donor or low polar media favored the occurrence of the LE state (Figure 1A−C). 46 The fluorescence profiles of the dyes 3k and 3j were almost totally determined by the CT state at 476 nm and that of excited state showed to be highly stable with a prevalence inclusive in nonpolar media, such as hydrocarbons (n-hexane and n-heptane).…”
Section: Resultsmentioning
confidence: 99%
“…As a fundamental platform, we employed three fluorescent dyes of N 46 Previously, we demonstrated that the balance between the CT and LE states can be modulated by solvent changes, finding a dominant and intense CT state in hydrogen-donor media, such as water, methanol, and ethanol, whereas the nonhydrogen donor or low polar media favored the occurrence of the LE state (Figure 1A−C). 46 The fluorescence profiles of the dyes 3k and 3j were almost totally determined by the CT state at 476 nm and that of excited state showed to be highly stable with a prevalence inclusive in nonpolar media, such as hydrocarbons (n-hexane and n-heptane). The relative abundance of these excited LE and CT states was confirmed by lifetime measurements, finding a dominant long-lived state (∼80%, 10−14 ns) (CT state) and a minority short-lived state (∼20%) (LE state) for the high CT-probes 3j and 3k in ethanol media.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations